On the number of inductively minimal geometries - Cara, Philippe (2013)
We count the number of inductively minimal geometries for any given rank by exhibiting a correspondence between the inductively minimal geometries of rank n and the trees with n+1 vertices. The proof of this correspondence uses the van Rooij–Wilf characterization of line graphs (see [11]).